Optimasi Waktu Perendaman dan Waktu Ekstraksi Pembuatan Gelatin dari Sisik Ikan Nila Hitam (Oreocharomis niloticus) sebagai Gelling Agent: Optimization of Soaking Time and Extraction Time for Making Gelatin from Black Tilapia (Oreocharomis niloticus) Fish Scales as a Gelling Agent - Rini Ambarwati; Septia Andini; Siti Salwah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Almost about 3/4 of the total weight of tilapia is waste, so the use of tilapia scale waste as gelatin has not been widely done. This study was designed to determine the effect of soaking and optimum extraction time on gelatin quality and determine the optimum conditions of soaking time and extraction time with Central Composite Design (CCD) design and optimum conditions determined by Response Composite Design (RSM). The conditions to be designed are to use 2 independent variables with variations in soaking time (12 hours, 24 hours, and 36 hours) and variations in extraction time (1 hour, 2 hours, and 3 hours) and the response to be seen is yield (%), viscosity (cP), and pH. The results of the study obtained the optimum condition of soaking time of 27,082 hours and extraction time of 2,989 hours, with a yield of 3.4356%, viscosity of 2.3933 cP and pH 3.8107, with the results of organoleptic evaluation parameters (brownish clear, coarse powder texture, typical tilapia aroma), yield (3.4356%.), pH (3.8107), water content (7.66%), ash content (0.18%), gelatin identification (positive biuret, millon and xantoprotein), viscosity (2.3933 cP), protein content (90.91%) and gel strength 5.417 (Bloom). Keywords: Gelatin, Ossein, Black tilipia scales Abstrak Hampir sekitar ¾ dari berat total ikan nila merupakan limbahnya, sehingga pemanfaatan limbah sisik ikan nila sebagai gelatin belum banyak dilakukan. Penelitian ini dirancang untuk mengetahui adanya pengaruh perendaman dan waktu ekstraksi optimum terhadap mutu gelatin dan mengetahu kondisi optimum waktu perendaman dan waktu ekstraksi dengan rancangan Central Composite Design (CCD) dan kondisi optimum ditentukan dengan Respon Composite Design (RSM). Kondisi yang akan dirancang adalah dengan menggunakan 2 variabel indipenden dengan variasi waktu perendaman (12 jam, 24 jam, dan 36 jam) dan variasi waktu ekstraksi (1 jam, 2 jam, dan 3 jam) dan respon yang akan dilihat yaitu rendemen (%), viskositas (cP), dan pH. Hasil penelitian didapatkan kondisi optimum waktu perendaman 27.082 jam dan waktu ekstraksi 2.989 jam, dengan rendemen 3.4356%, viskositas 2.3933 cP dan pH 3.8107, dengan hasil parameter evalusi organoleptik (berwarna bening kecoklatan, bertektur serbuk kasar, beraroma khas ikan nila), rendemen (3.4356%.), pH (3.8107), kadar air (7.66%), kadar abu (0.18%), identifikasi gelatin (positif biuret, millon dan xantoprotein), viskositas (2.3933 cP), kadar protein (90.91%) dan kekuatan gel 5.417 (Bloom). Kata Kunci: Gelatin, ossein, Sisik Nila Hitam